The impact of Margaret Thatcher's reforms in Britain - Paličková, Iveta (2005)
The thesis will trace Margaret Thatcher's reforms and their influence on British society. It will focus on her politics with regard to the monetary policy, privatisation, inflation, the Trade Unions and the Falklands War. It will seek to show the opposing views on Thatcher's reforms and their impact